PEMAHAMAN DAN LEGALITAS UCAPAN TALAK OLEH MASYARAKAT BANJAR DAN MENURUT KITABUN NIKAH SYAIKH ARSYAD AL-BANJARI - Sarmiji Sarmiji; M. Hanafiah, Inawati Mohammad Jainie Jarajap, Anwar Hafidzi, Abdul Hamid Karim (INTELIGENSIA MEDIA, 2022)
Divorce in marriage is the untying of the knot that binds husband and wife in order to break and terminate their connection. However, divorce in practice contains a concept that may not be consistent with the rules of the Qur'an and Sunnah. This work employs an empirical research approach (Field research) or seeks sources of research data by conducting direct interviews with informants in the field linked to the subject under investigation. The findings of this study indicate that the Banjar community's understanding of divorce utterances is based on the meanings contained in the pronunciations spoken by husbands to their wives, namely the meanings of divorces, which are primarily based on the Syafi'iyyah school of thought and are consistent with the kitabun nikah written by Shaykh Arsyad al-Banjari about the many pronunciations and fall of divorce.